The association between circadian rest-activity patterns and the behavioral and psychological symptoms depending on the cognitive status in Japanese nursing-home residents. (2nd December 2018) - Saito, Yuma; Kume, Yu; Kodama, Ayuto; Sato, Kotaro; Yasuba, Megumi
ABSTRACT: Background : Limited information is available on the relationship between sleep disturbances during nighttime and the behavioral and psychological symptoms of dementia in older nursing-home residents. However, a few reports on the association between the circadian rest-activity rhythm and the behavioral and psychological symptoms of dementia in older residents have been published. The main objective of the present study was to examine the association among the circadian rest-activity rhythm, behavioral and psychological symptoms, and the cognitive function status among older individuals living in facilities. Method : The investigation was conducted from September 2017 to February 2018, and participants were recruited from five nursing homes in Akita prefecture, Japan, after obtaining patient agreement to participate in the study. To measure nonparametric circadian rest-activity parameters such as interdaily stability, intradaily variability, relative amplitude, mean of the least active 5-h period, and mean of the most active 10-h period, Actigraph devices were worn on the participants' nondominant wrists continuously for seven days. The score or classification of the cognitive status and the severity of the behavioral and psychological symptoms of dementia (BPSD) were assessed using the clinical dementia rating (CDR) and the dementia behavior disturbance scale (DBD), respectively. The binomial logistic regression model was applied to clarify which kinds of circadian rest-activity parameters predicted the cognitive status in nursing home residents as well as the BPSD outcome. A multi-level model was also used to examine the association between the nonparametric rest-activity parameters and the BPSD outcome explained by the cognitive status among older individuals in facilities. Results : Seventy-seven participants (49 residents with dementia, and 28 residents without dementia) were included in this study. According to the binomial logistic regression analysis after adjusting for covariates, the classification of the cognitive status for older residents was associated with the DBD score (odds ratio, 1.22; 95% confidence interval [CI], 1.08, 1.38; p  < 0.001), the IS (odds ratio, 0.01; 95% CI, 0.00, 1.00; p  = 0.05) and the L5 (odds ratio, 0.99; 95% CI, 0.99, 1.00; p  = 0.05). The results of a multi-level model also indicated that the IV at individual-level was significantly associated with the DBD score for nursing home residents, with the CDR score at cluster-level as an explanatory variable. As well, a significant association between the RA at individual level and the DBD score was observed in a multi-level model explained by the CDR score at cluster-level. Conclusion : Of these models, the multi-level model provided grounds for our proposal that the fragmentation or the amplitude of rest-activity parameters might be associated with the outcome of BPSD, considering the cognitive status of older individuals in different facilities. The findings offer practical insight into the prevention of BPSD and the improvement of rest-activity rhythms in rehabilitative care in nursing homes.